2021
DOI: 10.3389/fonc.2021.727130
|View full text |Cite
|
Sign up to set email alerts
|

Proteome Analysis of Camellia nitidissima Chi Revealed Its Role in Colon Cancer Through the Apoptosis and Ferroptosis Pathway

Abstract: Colon cancer is the third most common cancer in the world with a high mortality rate. At present, surgery combined with radiotherapy and chemotherapy is the primary treatment, but patient prognosis remains poor. Traditional Chinese medicine (TCM) has become a complementary and alternative source of anti-cancer drugs. Camellia nitidissima Chi (CNC) is a TCM used to treat a variety of cancers. However, the role of CNC in cancer remains elusive, and its effect and mechanism on colon cancer have not been reported.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 36 publications
0
10
0
Order By: Relevance
“…We first assessed the effect of GA on the proliferation of HCC1806 cells by MTT and plate clone formation assays. The results showed that GA could inhibit HCC1806 cells proliferation in a dose-and time-dependent manner ( Zeng et al, 2020 ; Chen et al, 2021 ). Meanwhile, we found that the morphology of HCC1806 cells changed significantly after GA treatment, the number of HCC1806 cells decreased and the cells were in an apoptotic state.…”
Section: Discussionmentioning
confidence: 99%
“…We first assessed the effect of GA on the proliferation of HCC1806 cells by MTT and plate clone formation assays. The results showed that GA could inhibit HCC1806 cells proliferation in a dose-and time-dependent manner ( Zeng et al, 2020 ; Chen et al, 2021 ). Meanwhile, we found that the morphology of HCC1806 cells changed significantly after GA treatment, the number of HCC1806 cells decreased and the cells were in an apoptotic state.…”
Section: Discussionmentioning
confidence: 99%
“…The key event in ferroptosis is cell membrane damage associated with peroxidation of lipids (24). GPX4, which is an antioxidant enzyme that reduces ROS, can prevent the formation of toxic lipid peroxides (17,21). Inhibition of GPX4 activity results in ferroptotic cell death.…”
Section: Elevated Gpx4 and Ferrous Iron Are Potential Therapeutic Tar...mentioning
confidence: 99%
“…Iron accumulation, particularly ferrous iron (Fe 2+ ), can create ROS by participating in the Fenton reaction, thereby triggering ferroptosis (18). Additionally, the lipid ROS scavenger gutathione peroxidase 4 (GPX4) can convert lipid peroxides into non-toxic lipid alcohols to protect cells against ferroptotic death (19)(20)(21). Drug-tolerant persister breast cancer cells are vulnerable to ferroptosis induced by GPX4 inhibition (16).…”
Section: Introductionmentioning
confidence: 99%
“…Further mechanistic studies using proteomic and functional clustering analyses showed that AUCAN treatment upregulated 24 proteins and downregulated 42 proteins, suggesting that AUCAN treatment may regulate multiple genes in CRC. Chen et al (2021)conducted a label-free based quantitative proteomic analysis to evaluate the protein expression profiles in colon cancer cells treated with the traditional Chinese medicine Camellia nitidissima Chi (CNC). They showed that CNC regulated CRC cell proliferation via regulation of ferroptosis signaling.…”
Section: Proteomicsmentioning
confidence: 99%